Diagnosis of the current state of the assessment of the physical condition of women in the climacteric stage (Original) (Revista científica Olimpia, 2019)
In the climacterium-menopause stage there are biological transformations that affect the physical and mental state of the woman. In middle age, improving physical condition is vital to achieve the demands of daily activities. A healthy physical condition is achieved through systematic physical exercise, correctly dosed, that improves the physical and health levels achieved in previous periods. At this stage, there is a decline in physical capacities and chronic noncommunicable diseases arise or increase, unfavorable for the quality of life. In line with the foregoing, it is important to know how the physical condition of the woman in the climacteric stage behaves, in order to be able to evaluate it adequately and provide her with adequate possibilities of physical exercise to improve her health.
Keywords: climacteric; menospausia; physical condition; evaluation; physical exercise